MANAJEMEN SISTEM POIN DALAM MEMBINA KEDISIPLINAN SISWA - Erwin Susanto (UNIVERSITAS BENGKULU, 2015)
The purpose of the research is to describe the management of the point system in the formation student discipline at State of Senoir High School 4 Lubuklinggau. The research used thedescriptive qualitative method. The subject of research involved the principal, the vice of principal student affair, teacher, and the students. Data collection techniques through the observation, interview, and document. This research concluded that the management of the point system in the formation student discipline at school have described by the proces is like: the planning, the organizing, the actuating, the monitoring and evaluation, and the factor supporting and difficulty of the management of the point system.Keyword: management, point system, discipline